Oral candidiasis in HIV+ patients under treatment with protease inhibitors - Andréa Lusvarghi Witzel; Fernando Ricardo Xavier da Silveira; Maria de Fátima Costa Pires; Mônica Andrade Lotufo (Brazilian Oral Research, 2008)
The purpose of this work was to evaluate the influence of Protease Inhibitors (PI) on the occurrence of oral candidiasis in 111 HIV+ patients under PI therapy (Group A). The controls consisted of 56 patients that were not using PI drugs (Group B) and 26 patients that were not using any drugs for HIV therapy (Group C). The patient's cd4 cell counts were taken in account for the correlations. One hundred and ninety three patients were evaluated. The PI did not affect the prevalence of oral candidiasis (p = 0.158) or the frequency of C. albicans isolates (p = 0.133). Patients with lower cd4 cell counts showed a higher frequency of C. albicans isolates (p = 0.046) and a greater occurrence of oral candidiasis (p = 0.036).